Formando futuros: plataforma de cursos alinhada com a missão da ods 4 - COLEN, Felipe Maximo; OLIVEIRA, Rafael Nascimento; SILVA, Jefferson Messias da; SANTOS, Paulo Victor Reis; SILVA, Brenda Garcia M. da; ANDRADE, Sabrina Lima de; RAMOS, Gustavo Oliveira Postigo (217, 2024)
Educational inequality is a significant global challenge, limiting development opportunities for millions of people and aligning with the United Nations Sustainable Development Goal 4 (SDG 4), which aims to ensure quality education for all. In response to this challenge, the ScireClass platform was created, a digital tool dedicated to the promotion and sale of online courses. The project was structured using the agile Scrum methodology, which provided efficient organization of activities and ensured timely delivery. ScireClass was developed for mobile devices, with databases and media stored in the cloud, guaranteeing accessibility and security for users. The system stands out for its proposal to democratize access to quality education, promoting continuous learning and contributing to educational inclusion, thus aligning with global development goals.

Educational inequality is a significant global challenge, limiting development opportunities for millions of people and aligning with the United Nations Sustainable Development Goal 4 (SDG 4), which aims to ensure quality education for all. In response to this challenge, the ScireClass platform was created, a digital tool dedicated to the promotion and sale of online courses. The project was structured using the agile Scrum methodology, which provided efficient organization of activities and ensured timely delivery. ScireClass was developed for mobile devices, with databases and media stored in the cloud, guaranteeing accessibility and security for users. The system stands out for its proposal to democratize access to quality education, promoting continuous learning and contributing to educational inclusion, thus aligning with global development goals.

La desigualdad educativa es un desafío global significativo que limita las oportunidades de desarrollo para millones de personas y se alinea con el Objetivo de Desarrollo Sostenible 4 (ODS 4) de las Naciones Unidas, que busca garantizar una educación de calidad para todos. En respuesta a este desafío, se creó la plataforma ScireClass, una herramienta digital dedicada a la promoción y venta de cursos en línea. El proyecto se estructuró utilizando la metodología ágil Scrum, lo que proporcionó una organización eficiente de las actividades y garantizó la entrega en el tiempo previsto. ScireClass se desarrolló para dispositivos móviles, con bases de datos y medios almacenados en la nube, garantizando accesibilidad y seguridad para los usuarios. El sistema destaca por su propuesta de democratizar el acceso a una educación de calidad, promoviendo el aprendizaje continuo y contribuyendo a la inclusión educativa, alineándose con los objetivos de desarrollo global.
Shaping futures: a course platform aligned with the mission of SDG 4
Formando futuros: plataforma de cursos con la misión del ODS 4
Keywords: Inclusão digital; Informação e Comunicação